Gendered Trajectories : Women, Work, and Social Change in Japan and Taiwan. - Yu, Wei-hsin (Stanford University Press, 2009)
Through a detailed analysis of macroeconomic changes and individuals' lifetime employment trajectories, this book explains why Japan and Taiwan have experienced different levels of improvement in women's economic status over the last half century.